Resumes for the health care professional - Marino, Kim (Wiley & Sons, 2000)
The burgeoning health care industry expects to add 3 million new jobs by the end of this century. In order to take advantage of these opportunites, you'll need a strong resume. A step-by-step, no-nonsense approach to resume writing is offered by providing over 100 samples you can use to give your resume a professionally designed look. Also included are sample cover letters and thank you letters, ``how-to'' information, job and interview tips, job search techniques, 25 tough questions most often asked by hospital interviewers, answers to these questions, and key questions you should ask in return.